Endoscopic submucosal dissection: a country dissemination experience and outcomes. Issue 10 (24th August 2022) - Rodríguez-Carrasco, Marta; Libânio, Diogo; Pimentel-Nunes, Pedro; Barreiro, Pedro; Ferreira, Anibal; Küttner-Magalhães, Ricardo; Pinho, Rolando; Boal Carvalho, Pedro; Areia, Miguel; Lage, Jorge; Serrano, Miguel; Silva, João; et al.
Abstract : Objective: An increasing use of endoscopic submucosal dissection (ESD) has been reported in Western countries, although some differences in training schemes and outcomes have been described. We aimed to report the training model, implementation, and outcomes of ESD in Portugal. Methods: All endoscopists trained at our center from our country ( n = 9) were invited to a survey regarding: (a) training period; (b) ESD outcomes and (c) implementation of ESD in each respective center. Results: All endoscopists completed the survey. Learning ESD was centered on human ESD assistance in a high-volume center during a median time of 6 months and complemented mainly by hands-on courses (89%). During the surveyed period, a total of 1229 ESD were performed, mostly in gastric locations (74%). Median complete R0 and curative resection rate were 92% (IQR, 81–96.8) and 87% (IQR, 74–93.3), respectively, and median perforation rate was 0.89% (IQR, 0.25–6.22). The main limitations encountered during the implementation of ESD were related to the lack of initial mentoring or insufficient expertise to progress to more difficult lesions. Conclusion: Learning ESD through participation in hands-on courses and visiting high-volume centers seems to be adequate to achieve a good competence at the initial stage of ESD, which in fact is in consonance with the European Society of Gastrointestinal Endoscopy recommendations. However, mentoring is essential for technical progression, and this represents the fundamental barrier during the adoption of ESD, which may be overcome by increasing hands-on training in animal or artificial simulators, but preferably with the implementation of a structured training program.